АНАЛІЗ ВПЛИВУ ХАРАКТЕРИСТИК ПОТУЖНОСТІ СИНХРОННИХ ГЕНЕРАТОРІВ НА ПРОПУСКНУ ЗДАТНІСТЬ ПЕРЕТИНІВ ОЕС УКРАЇНИ - Лук’яненко , Л.М. (Інститут електродинаміки НАН України, Київ, 2014)
In the paper, one of main limitations of total transfer capacity (TTC) of interfaces in IPS of Ukraine were briefly analysed. Also general approaches how to take into account the PQ characteristics of synchronous generators (SG) during the calculation TTC of controlled interfaces were considered. As example, the impact PQ characteristics of SG (with and without consideration them voltage dependence) on TTC of one interface was calculated. References 4, figure 1.